Diabetic foot ulcer classifications: A critical review. (16th March 2020) - Monteiro‐Soares, Matilde; Boyko, Edward J.; Jeffcoate, William; Mills, Joseph L.; Russell, David; Morbach, Stephan; Game, Fran
Abstract: Classification and scoring systems can help both clinical management and audit outcomes of routine care. The aim of this study was to assess published systems of diabetic foot ulcers (DFUs) to determine which should be recommended for a given clinical purpose. Published classifications had to have been validated in populations of > 75% people with diabetes and a foot ulcer. Each study was assessed for internal and external validity and reliability. Eight key factors associated with failure to heal were identified from large clinical series and each classification was scored on the number of these key factors included. Classifications were then arranged according to their proposed purpose into one or more of four groups: (a) aid communication between health professionals, (b) predict clinical outcome of individual ulcers, (c) aid clinical management decision making for an individual case, and (d) audit to compare outcome in different populations. Thirty‐seven classification systems were identified of which 18 were excluded for not being validated in a population of >75% DFUs. The included 19 classifications had different purposes and were derived from different populations. Only six were developed in multicentre studies, just 13 were externally validated, and very few had evaluated reliability.Classifications varied in the number (4 ‐ 30), and definition of individual items and the diagnostic tools required. Clinical outcomes were not standardized but included ulcer‐free survival, ulcer healing, hospitalization, limb amputation, mortality, and cost. Despite the limitations, there was sufficient evidence to make recommendations on the use of particular classifications for the indications listed above.